Preventing ventilator-associated pneumonia: A position paper of the International Society for Infectious Diseases, 2024 update - Victor Daniel Rosenthal; Ziad A. Memish; Gonzalo Bearman (International Journal of Infectious Diseases)
Objectives: This review by a panel of experts convened by the International Society for Infectious Diseases aims to consolidate current recommendations for preventing ventilator-associated pneumonia (VAP). It provides insights into VAP rates, the attributable extra length of stay, costs, mortality, and risk factors in high-income and low- and middle-income countries (LMICs). Methods: A comprehensive review of existing recommendations and evidence-based strategies for preventing VAP was conducted. The expert panel analyzed data on VAP incidence, associated healthcare burdens, and risk factors across different economic settings to formulate applicable preventive measures. Results: The review identifies significant differences in VAP rates, healthcare costs, extra length of hospital stay, and mortality between high-income and LMICs. Evidence-based strategies for preventing VAP were highlighted, demonstrating their effectiveness across different healthcare settings. Conclusion: The recommendations and insights provided in this position paper aim to guide healthcare professionals in effectively preventing VAP. The adoption of evidence-based preventive strategies can potentially reduce VAP rates, and associated costs, and improve patient outcomes in both high-income and LMICs.